2014
DOI: 10.1007/s12079-014-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen differentially affects the hox proteins Hoxb5 and Hoxa5 altering airway branching and lung vascular formation

Abstract: Hoxb5 and Hoxa5 transcription factor proteins uniquely impact lung morphogenesis at the developmental time point when extremely preterm infants are born. The effect of O 2 exposure (0.4 FiO 2 ) used in preterm infant care on these Hox proteins is unknown. We used ex vivo fetal mouse lung organ cultures to explore the effects of 0.4 FiO 2 on lung airway and vascular formation in the context of Hoxb5 and Hoxa5 expression and regulation. Compared to room air, 48 h (h) 0.4 FiO 2 adversely attenuated airway and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…In accordance with our theory, in 2005 Rhoads et al reported on a reduction of VEGFR-2 at the mRNA and protein level in cells expressing Hoxa5 [59]. Further work by Mujahid et al (2013) and Silfa-Mazara (2014) showed interactions between Hoxa5 and VEGFR-2, whereby the amount of VEGFR-2-positive cells in a fetal lung mouse model was altered by miRNA influence, followed by a reduction in the formation of vascular plexuses around the terminal airways. These findings could be associated with the observed changes in Hoxa5 localization [28].…”
Section: The Influence Of Mirna On Kdr Expressionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with our theory, in 2005 Rhoads et al reported on a reduction of VEGFR-2 at the mRNA and protein level in cells expressing Hoxa5 [59]. Further work by Mujahid et al (2013) and Silfa-Mazara (2014) showed interactions between Hoxa5 and VEGFR-2, whereby the amount of VEGFR-2-positive cells in a fetal lung mouse model was altered by miRNA influence, followed by a reduction in the formation of vascular plexuses around the terminal airways. These findings could be associated with the observed changes in Hoxa5 localization [28].…”
Section: The Influence Of Mirna On Kdr Expressionsupporting
confidence: 87%
“…One interesting candidate seems to be Hoxa5, which is directly regulated by miR-130a-3p [58]. Hoxa5 is known for its important role during embryonic and fetal development of the CNS as well as for an anti-angiogenic effect inter alia through reduction of VEGFR-2 [59,60]. In the present study we could demonstrate that miR-130a-3p indirectly modulated Kdr expression in primary sensory neurons.…”
Section: The Influence Of Mirna On Kdr Expressionsupporting
confidence: 53%
“…Hong et al found that HOXB5 increases cell invasion and migration in human gastric carcinoma by regulating β‐catenin. Additionally, a reduction of HOXB5 in mesenchymal cells reportedly facilitates apoptosis . Interference of HOXB5 causes apoptosis in vagal and trunk neural crest cells of mice .…”
Section: Discussionmentioning
confidence: 97%
“…Abnormal expression of HOXB5 modulates cell viability and proliferation in various cancers, such as non‐small cell lung cancer, breast cancer, osteosarcoma, retinoblastoma, oral squamous cell carcinoma, and gastric carcinoma . HOXB5 also is a significant regulator of mesenchymal cell apoptosis …”
Section: Introductionmentioning
confidence: 99%